Retraction notice for “Temperature and Mass Profile of Far-infrared Skeleton Nebula” - Board, Editorial (Himalayan Physics, 2018)
On 2nd January 2018 the Editorial Board of Himalayan Physics agreed to retract the article ‘Temperature and Mass Profile of Far-infrared Skeleton Nebula’ published in Himalayan Physics, Vol.6&7 pp.1-4 (DOI: http://dx.doi.org/10.3126/hj.v6i0.18348) because it is a duplication of an article published in Himalayan Physics Vol.1 2010 pp.1-3 (DOI: http://dx.doi.org/10.3126/hj.v1i0.5162) Editorial Board, Himalayan Physics 2nd January 2018